Validation of the names linked to the oldest fossil Connaraceae wood (Connaroxylon, Connaroxylon dimorphum) - Baas, Pieter; Manchester, Steven; Wheeler, Elisabeth A.; Srivastava, Rashmi (Phytotaxa, 2022)
N/A